2014
DOI: 10.1002/psp.1846
|View full text |Cite
|
Sign up to set email alerts
|

Civic Stratification and Social Positioning: CEE Labour Migrants without a Work Permit

Abstract: Civic stratification is a relatively new dimension of social inequality in contemporary Western societies. States grant, or deny, different legal statuses and related social and economic rights. European Union (EU) nationals, for instance, have full rights to settle and work in other EU countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…However, the majority of studies focus on sociology and demography. One study found significant social class differences within RMP groups, in what is known as social stratification, and the initial understanding of the RMP as a whole was gradually displaced [15,16]. Another study found that more distinctions between individual and sometimes micro-communities are coming to be universally acknowledged [17].…”
Section: Internal Differentiation Of Migrantsmentioning
confidence: 99%
“…However, the majority of studies focus on sociology and demography. One study found significant social class differences within RMP groups, in what is known as social stratification, and the initial understanding of the RMP as a whole was gradually displaced [15,16]. Another study found that more distinctions between individual and sometimes micro-communities are coming to be universally acknowledged [17].…”
Section: Internal Differentiation Of Migrantsmentioning
confidence: 99%
“…The free movement of people is regarded as an important component in ‘creating a European employment market’ (Eurobarometer, 2004 ; Heinz & Ward-Warmedinger, 2006 , p. 7), whereby EU citizens are obliged to have comprehensive resources at their disposal so as not burden the welfare state system of their host countries. Having a working relationship or contract (with a company, an employer or with themselves as self-employed) is therefore a defining element of their legal status (Rosewarne, 2010 ; Ruhs & Anderson, 2010 ; Snel, Faber, & Engbersen, 2015 ). Consequently, mobile citizens are de facto mobile workers on a mobile market .…”
Section: The Commodification Of European Mobile Workmentioning
confidence: 99%
“…(Amcoff & Niedomysl, ; Bell et al, ; Camara & Garcia‐Roman, ; Clark, Duque‐Calvache, & Palomares‐Linares, ; Johnston, Poulsen, & Forrest, ; Mberu & Mutua, ; Mezger Kveder & Beauchemin, ; Midouhas & Flouri, ; Snel, Faber, & Engbersen, ; Svensson, Lundholm, De Luna, & Malmberg, ; Wang, Guo, & Cheng, ; Wilson, ; Yang, Noah, & Shoff, )…”
Section: Assemblage Thinking and Population Geographyunclassified